Vital Perfusion-Fixation Technique Through Carotid Arteries for Preparation of Histologic Sections from Periodontium and Jaw Bone of Dog - AA - Basiri; M Atabaki; Sh Adibi (Isfahan University of Medical Sciences, 2005)
processing of tissues before histologic slices is necessary for preparation of proper histologic sections in animal studies. Fixation is one of the most important and early laboratory stages of tissue processing. Amount of penetration time of fixator material, into deep layers and central portions of hard tissues, is important factor for prevention of cell lysis. The purpose of vital perfusion technique is immediate and rapid fixation of tissue, before tissue lysis and necrosis.After general anesthesia, the common carotid artery and jugular vein were isolated through a vertical incision and dissection of muscles, in both sides of the neck. The carotid arteries, were clamped, then normal saline and 10 percent formalin were injected respectively, through one branole. While heart rate and respiration slowed down, the content of jaw vessels were normal saline and formalin. Oral mucosa became completely pale and muscles got stiff. Formalin was observed in vessels and between tissues.The histologic sections had favorable quality. Signs of tissue lysis were not observed and small vessels were also empty from blood. The vital perfusion fixation technique from carotid arteries can make rapid fixation of the periodontal tissue and jaw bone of dog and prevent tissue changes. This method can facilitate other laboratory stages for preparation of histologic sections.Key words. Vital perfusion fixation, Histologic section, Carotid artery, Periodontium, Jaw bone, Dog.